Evaluación Presupuestaria Al Gobierno Autónomo Descentralizado Parroquial Rural De Milagros Del Cantón Pindal, Periodo 2020 - 2021. - Ortega Ortega, Joanna Patricia (2023)
The present thesis work called "BUDGET EVALUATION TO THE RURAL PARISH DECENTRALIZED AUTONOMOUS GOVERNMENT OF MILAGROS, PERIODS 2020 - 2021", was carried out in accordance with the Academic Regime Regulations of the National University of Loja prior to opting for the degree and title of Accounting Engineer. and Audit, Public Accountant-Auditor and with the purpose of evaluating the execution of projects and established in the Annual Operating Plan, measuring the efficiency and effectiveness of the budget through the application of budgetary indicators and finally the preparation of a report of the results obtained that It constitutes a support tool for the authorities of the entity. In order to comply with the objectives of the thesis work, the collection of information was carried out such as the initial budget, budgetary documents, state of execution and the annual operating plan; so that in the latter it was identified that the established projects are not fully executed given that for the 2020 period, 4 of 11 planned projects were achieved, which represents an execution of 36.36%, that is, that in Monetary values of $122,578.28 were executed since due to the worldwide confinement due to the Covid-19 pandemic, the GAD administration did not work normally and by the year 2021 compliance with 3 of 14 scheduled projects was carried out, which represents an execution of the POA of 21.43% for a total of $46,403.80 mainly due to the fact that the Autonomous Government does not have its own trucking team to carry out activities aimed at road maintenance. Subsequently, to measure the efficiency of budget execution, budgetary indicators and indices were applied where it was evidenced that the Milagros Parish Government has a level of financial self-sufficiency for the year 2020 of 0.01% and 0.00% for the year 2021. which indicates that it does not have enough of its own income to cover its current expenses, it was determined that it does not have financial autonomy since for the 2020 period this was 0.002% and 0.00% for the 2021 period, demonstrating that the institution does not It has the financial capacity to finance itself through its management. On the other hand, it is evident that the Parish GAD has optimal levels of financial solvency since for each dollar it counts for the year 2020 with $2.68 and for the year 2021 with $0.90 to cover expenses from personnel expenses. Finally, the report that was made available to the highest authority of the Parish GAD was prepared, detailing the conclusions and recommendations based on the results obtained through the budgeted evaluation.